Applications of Carbon Nanotubes in the Internet of Things Era - Pang, Jinbo; Bachmatiuk, Alicja; Yang, Feng; Liu, Hong; Zhou, Weijia; Ruemmeli, Mark H.; Cuniberti, Gianaurelio (Giovanni) (Nano-Micro Letters, 2021)
Abstract: The post-Moore's era has boosted the progress in carbon nanotube-based transistors. Indeed, the 5G communication and cloud computing stimulate the research in applications of carbon nanotubes in electronic devices. In this perspective, we deliver the readers with the latest trends in carbon nanotube research, including high-frequency transistors, biomedical sensors and actuators, brain–machine interfaces, and flexible logic devices and energy storages. Future opportunities are given for calling on scientists and engineers into the emerging topics. [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2023-03-20
Keywords: Actuators; Brain–machine interfaces; Carbon nanotubes; Energy storage; Sensors; Transistors